Perceived Factors on the Performance of Graduates in the Licensure Examination (Asia Pacific Journal of Social and Behavioral Sciences, 2023)
Passing the licensure examination indicatesthe quality of education offered by an institution. A country requires this to its graduates to ascertain the effectiveness of jobs and employment that are vital to a country’s development. This study investigated factors affecting students’ performance in the licensure examination at one university in Mindanao, Philippines. The study employed a descriptive-survey research design utilizing Perceived Causes of Academic Failure Inventory (PCAFI) to help pinpoint factors and causes that contributed to the performance of graduates during the board examination. Results of the study showed that problems with the learning environment, specifically on “Many things to memorize,” and problems with the content examination, specifically on “Examination was very stressful,” were identified as the key factors of their performance in the licensure examination. The study recommended intervention programs and mechanisms in improving the conduct of board examination review programs in the university, which primarily address reducing test anxiety while improving test-taking skills and study strategies. It further recommended conducting studies using other designs and variables to ensure a more comprehensive understanding of results relative to students’ performance in the licensure examination.
Keywords: Perceived factors, licensure examination, performance, learning environment, content examination